The struggle for legitimacy in business and human rights regulation—a consideration of the processes leading to the UN Guiding Principles and an international treaty - Hamm, Brigitte (Human rights review, 2022)
After the UN Guiding Principles on Business and Human Rights (UNGPs) were adopted in 2011, an international treaty has been being negotiated since 2014. The two instruments reveal similarities and also conflicts regarding the adequate organization of the global economy based on human rights. The focus in this article will be on the processes leading to these instruments, because they themselves mirror different understandings of governance in the field of business and human rights as well as the struggle over the power of definition and legitimacy. The UNGPs were developed on the basis of global multi-stakeholder consultations, underlining legitimacy through broad inclusion. There are varying judgements as to the success of this approach. The process towards the treaty follows the traditional path of negotiations at UN level. These negotiations reveal a struggle for recognition of the legitimacy of the process itself. Both procedures have shortcomings with regard to legitimacy and show the need for a revision concerning the inclusion of stakeholders. The complementarity of a soft and hard law instrument may enhance the creation of a level playing field in the global economy, thereby strengthening human rights.